An Anion‐Tuned Solid Electrolyte Interphase with Fast Ion Transfer Kinetics for Stable Lithium Anodes. Issue 14 (17th February 2020) - Wang, Zhenxing; Qi, Fulai; Yin, Lichang; Shi, Ying; Sun, Chengguo; An, Baigang; Cheng, Hui‐Ming; Li, Feng
Abstract: The spatial distribution and transport characteristics of lithium ions (Li + ) in the electrochemical interface region of a lithium anode in a lithium ion battery directly determine Li + deposition behavior. The regulation of the Li + solvation sheath on the solid electrolyte interphase (SEI) by electrolyte chemistry is key but challenging. Here, 1 m lithium trifluoroacetate (LiTFA) is induced to the electrolyte to regulate the Li + solvation sheath, which significantly suppresses Li dendrite formation and enables a high Coulombic efficiency of 98.8% over 500 cycles. With its strong coordination between the carbonyl groups (CO) and Li +, TFA − modulates the environment of the Li + solvation sheath and facilitates fast desolvation kinetics. In addition, due to relatively smaller lowest unoccupied molecular orbital energy than solvents, TFA − has a preferential reduction to produce a stable SEI with uniform distribution of LiF and Li2 O. Such stable SEI effectively reduces the energy barrier for Li + diffusion, contributing to low nucleation overpotential, fast ion transfer kinetics, and uniform Li + deposition with high cycling stability. This work provides an alternative insight into the design of interface chemistry in terms of regulating anions in the Li + solvation sheath. It is anticipated that this anion‐tuned strategy will pave the way to construct stable SEIs for other battery systems. Abstract : This work adopts lithium trifluoroacetate as the sacrificial agent to regulate a Li + solvation sheath of a lithium anode in a lithium ion battery, which not only ensures low energy barrier for Li + desolvation at a solid electrolyte interphase (SEI)/electrolyte interface, but produces a stable SEI with more ion channels to reduce the Li + diffusion energy barrier and enables uniform Li + deposition with high cycling stability.